2021
DOI: 10.2147/jmdh.s301346
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional Education Competition During the COVID-19 Pandemic at King Saud University: Benefits and Challenges

Abstract: Background The objective of this qualitative study was to explore the value of virtual IPE competition that involved a COVID-19 case among healthcare students and the lessons that can be learned to improve this experience in the future. Methods The 27 senior students from the colleges of medicine, pharmacy, nursing, and paramedics were invited to two focus groups that followed the IPE competition and lasted 60 minutes each. A semi-structured focus group discussion guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The transition from face-to-face IPE to ERT imposed challenges regarding meeting learning outcomes, and access to IPE. Even though our case reports indicated that the intended learning outcomes remained the same during ERT, facilitators still had to ensure that those were addressed adequately by the new mode of delivery (Alrasheed et al, 2021).If IPE continues to be offered online or as a hybrid model, evaluation and assessments of the attained learning outcomes are warranted. Nonetheless, advantages of remote and online learning in IPE should not be overlooked.…”
Section: Remote and Online Learningmentioning
confidence: 90%
“…The transition from face-to-face IPE to ERT imposed challenges regarding meeting learning outcomes, and access to IPE. Even though our case reports indicated that the intended learning outcomes remained the same during ERT, facilitators still had to ensure that those were addressed adequately by the new mode of delivery (Alrasheed et al, 2021).If IPE continues to be offered online or as a hybrid model, evaluation and assessments of the attained learning outcomes are warranted. Nonetheless, advantages of remote and online learning in IPE should not be overlooked.…”
Section: Remote and Online Learningmentioning
confidence: 90%
“…Three of the studies focused on IPE-specific classes. The majority of students who participated in virtual IPE activities reported high levels of satisfaction and agreed or strongly agreed that activities helped clarified professional roles, improved communication and teamwork, and improved confidence levels [9,10,21].…”
Section: Characteristics Of Selected Studiesmentioning
confidence: 97%
“…In the article by Farahani et al, more than 95% of participants stated that more instructional videos should be included within all lab-based classes [24]. Three of the studies reported telehealth as a theme and noted the benefit and importance of being able to mimic emerging telehealth practices in pharmacy practice using web conferencing platforms [16,18,21]. Only one study focused on students' opinions relating to virtual versus in-person learning after returning to in-person learning, and students in this study expressed a strong preference for in-person labs after having virtual labs the previous year [22].…”
Section: Characteristics Of Selected Studiesmentioning
confidence: 99%
“…The educational content for IPE in prescribing in primary care sessions was originally developed for face to face teaching delivery in 2019 and shifted to the remote setting due to the Covid-19 outbreak. Published literature showed the lessons learnt from the innovative trials of emergency remote teaching during the Covid-19 pandemic and suggested exploring the virtual IPE models further [18][19][20]. In order to maintain the effective teaching delivery and student engagement during the remote sessions, video communication and online polling tools were added as an interactive component to the IPE sessions at UCL School of Pharmacy.…”
Section: Introductionmentioning
confidence: 99%